Strategi Pembelajaran Pendidikan Agama Islam dalam Penguatan Kepribadian Siswa - Koyin, Nur (IEMJ: Islamic Education and Management Journal, 2024)
This research aims to explore Islamic religious education learning strategies in strengthening students' personality formation. This research is categorised as qualitative research in the form of literature study. This research approach is a descriptive approach. The research data uses a variety of scientific literature that correlates with the subject matter. Meanwhile, data analysis uses the stages of reduction, presentation, and verification. The results showed that there are a number of Islamic religious education learning strategies in strengthening the formation of students' personalities, including political strategies that affect various fields of life, including education, such as aspects of the education curriculum. Then the cultural strategy as an efficient cultural approach using cultural symbols. Next, a socio-cultural strategy aimed at making society more open. This research contributes to the importance of normative and contextual strategies in strengthening students' personalities through Islamic religious education learning.